Disagreements in the beginning of 20th century Lithuanian idealistic psychology on the question of consciousness - Gučas, A. (Psichologija, 1966)
The first statements on the conditionality of personal consciousness appear in the beginning of 20th century in the history of psychology in Lithuania written in Lithuanian (translations of Marxism classics). The attempts of the representatives of idealistic approach (Vydunas, R. Bytautas) to oppose the materialistic understanding of consciousness reveal great disagreements in idealistic psychology itself and strengthen the materialistic approach to human mind.